Improving tool of the transport logistics system - Solarov, Oleksandr; Batiuk, Maryna (ТзОВ «Галицька видавнича спілка», 2021)
The article examines the tools to improve transport logistics. The implementation of Blockchain in logistics will ensure the safety of data, protect the document repository from hacking, and eliminate the possibility of changing information about the transportation progress.
Keywords: 656.13